2021
DOI: 10.1016/j.heliyon.2021.e07455
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining COVID-19 pandemic lockdown era air pollution impact through utilization of more renewable energy resources

Abstract: The lock down engendered by COVID-19 pandemic has impacted positively on the environment through reduction of the emissions of green house gases, CO 2 , CO and other pollutants into the atmosphere below the pre-COVID-19 levels. There are fears that the gains made in the environment during COVID-19 may be frittered away as nations around the world make serious efforts to boost the COVID-19 recessed economy through massive investments in the sectors of the economy that are not environmentally friendly. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 55 publications
3
25
0
Order By: Relevance
“…While the decline in conventional energy consumption is positive from a sustainability perspective, COVID-19 has also led to a reduction in investment in renewable energy sources [126]. This state of affairs may also continue after the COVID-19 pandemic, as many countries see solutions to their economies hit by a pandemic recession by investing in industries that are not environmentally friendly [128]. It is also confirmed that during the COVID-19 pandemic, energy consumption strategies also shifted to more sustainable ones, especially in lower-income households where certain saving strategies were applied [129].…”
Section: Discussionmentioning
confidence: 99%
“…While the decline in conventional energy consumption is positive from a sustainability perspective, COVID-19 has also led to a reduction in investment in renewable energy sources [126]. This state of affairs may also continue after the COVID-19 pandemic, as many countries see solutions to their economies hit by a pandemic recession by investing in industries that are not environmentally friendly [128]. It is also confirmed that during the COVID-19 pandemic, energy consumption strategies also shifted to more sustainable ones, especially in lower-income households where certain saving strategies were applied [129].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there is necessary the disconnecting of economic growth from air pollution and the reduction of releases from the industrial segment (Magazzino et al, 2021 ). Hence, financing renewable energy resources will support the green and clean ecosystem produced by the COVID‐19 lockdown (Rita et al, 2021 ). In terms of mobility, in order to curtail traffic discharges, which considerably enhance air quality (Wu et al, 2021 ) and improve health, there is necessary the shift to environmentally friendly transport means.…”
Section: Concluding Remarks and Policy Implicationsmentioning
confidence: 99%
“…The health challenge caused by COVID‐19 pandemic was the most distressing event the humanity had seen in this generation (Rita et al, 2021 ). Until the end of December 2020, there were no definite antivirals or vaccine, and the standard epidemiological advice alike isolation, observation, and monitoring were employed (Reina, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, COP26 was held, and the goal of limiting global warming to 1.5 • C was discussed. Although CO 2 emissions during the COVID-19 diffusion period have been on a downward trend, the economy's recovery needs to be carried out in a green and smart way, rather than letting CO 2 emissions return to normal as the recovery progresses [13]. In some areas, new ventilation systems are already being proposed on the basis of measured data and simulations.…”
Section: Introductionmentioning
confidence: 99%